Effectiveness of cognitive stimulation for individuals with mild cognitive impairment: a systematic review and meta-analysis - Lu Hua Chen; Oi Ling Lee; Yan Wing Lee; Shu Ting Ng; Sum Yi Eugenia Ngai; Yat Hei Zita Pau; Tongyu Ma; Hon-lam Joseph Yuen (BMJ Open)
Objective Cognitive stimulation (CS) is a non-pharmacological intervention aimed at enhancing cognitive function. However, the effectiveness of CS in individuals diagnosed with mild cognitive impairment (MCI) remains inconclusive. Therefore, this study aimed to assess the effectiveness of CS in improving cognitive function, psychological well-being, instrumental activities of daily living (IADL) and quality of life (QoL) in individuals with MCI, based on randomised controlled trials (RCTs).Design Systematic review and meta-analysis.Data sources Six English databases were systematically searched, including PubMed, Web of Science, Embase, Cumulative Index to Nursing and Allied Health Literature, American Psychological Association PsycInfo and Academic Search Premier.Eligibility criteria RCTs about CS for individuals with MCI, published between January 2003 and December 2024.Data extraction and synthesis Data were extracted and assessed using the revised Cochrane risk of bias tool for randomised trials by independent researchers. The meta-analysis was conducted using the standardised mean difference (SMD) and 95% CIs of the included studies.Results The meta-analysis included five eligible studies for the primary outcomes of cognitive function and three eligible studies for the secondary outcomes of psychological wellness. In the pooled samples, the CS intervention had a significant effect on cognitive function (SMD=0.63, 95% CI 0.25 to 1.01; p=0.001) and depression symptoms (SMD=−0.29, 95% CI −0.55 to −0.03; p=0.03) in individuals with MCI. However, no significant improvements in anxiety symptoms were identified after the CS intervention (SMD=−0.05; 95% CI −0.31 to 0.21; p=0.71).Conclusion The CS intervention can effectively improve cognitive function and alleviate depression symptoms. Although a meta-analysis was not conducted for IADL and QoL due to the limited number of included studies, positive trends in enhancing IADL performance and augmenting QoL were observed in individuals with MCI. However, due to the scarcity of relevant studies in this research field, more comprehensive RCTs are warranted to provide a better understanding of the potential benefits of CS and to guide its clinical application in the future.PROSPERO registration number CRD42023494685.